Multidisciplinary rehabilitation and steroids in the management of multiple sclerosis relapses: a randomized controlled trial - Nedeljkovic, Una (Arch Med Sci, 2015)
INTRODUCTION: Periodic relapses are one of the main characteristics of multiple sclerosis (MS), from which recovery is often incomplete despite high-dose methylprednisolone (HDMP) treatment. The aim of our study was to evaluate the potential benefits of short-term HDMP combined with multidisciplinary rehabilitation (MDR) in persons with MS in relapse in order to assess whether combination of steroid therapy with MDR is more beneficial than steroid therapy alone. MATERIAL AND METHODS: This investigation was conducted as a randomized controlled trial. The MS patients were eligible if they had an established diagnosis and relapse requiring application of HDMP. Forty-nine patients were included in the study and randomized to control and treatment groups, and 37 completed the study. High-dose methylprednisolone was administered to all patients. The treatment group additionally underwent an MDR program over a 3-week period. All outcome measures were completed at baseline and 1 and 3 months later. RESULTS: The Expanded Disability Status Scale (EDSS) and Functional Independence Measure (FIM) motor scores improved statistically significantly 1 month after HDMP, in both treatment and control groups. During the study period, in the treatment group, a sustained large effect size (ES) was found for both physical and mental composite scores of Multiple Sclerosis Quality of Life-54 (MSQoL-54), while in the controls, a sustained moderate ES was demonstrated only for physical composite score. CONCLUSIONS: Our findings suggest that MDR improves MS relapse outcome.